HDI XMAS July 15, 2019. Geraldine Legge photos. - Barrett, Terra
A black and white photo of Calvin Legge, Gilbert Reid, Sam Bishop, Joseph Bishop, Dave Worthman, Elliot Reid, and Leslie Bishop at Geraldine's house.